Performance Analysis Of Agricultural Extensive In Indonesia Based On Farmer Group View - Hasanuddin (International Journal of Science, Technology & Management, 2022)
This study aims to determine the activities and performance of extension workers based on the perceptions of farmer groups in Makali District, Polman Regency. This type of research is descriptive research, namely research that describes the phenomenon of the research variables without testing the hypothesis. The research location is in Makali District, Polman Regency. The research population of the extension partners is the farmer group, totaling 60 farmer groups. A purposive sample assessment in which all the heads of the farmer groups were used as research samples representing their respective farmer groups. The results showed that the performance assessment of the extension workers in Matakali District, Polman Regency conducted by Extension Partners (Chairman of the Farmers Group) was 4096 points, which means that the performance of the extension workers in Matakali District, Polman Regency was in the Enough category. Several things that need to be done by extension workers in improving performance so that they are optimal are the preparation of extension planning data, application of extension methods, self-help and regional development, especially the development of the extension profession in creating scientific papers to be further improved and in accordance with the needs of extension workers and breeders in Makali District. Polman district